Alcohol drinking patterns among high school students in Ethiopia: a cross-sectional study - Reda Ayalu A; Moges Asmamaw; Wondmagegn Berhanu Y; Biadgilign Sibhatu (BMC, 2012)
Abstract Background Alcohol use is an important risk factor for morbidity, mortality and social harm among adolescents. There is paucity of data on alcohol use among high school students in Ethiopia. This study aimed to determine the prevalence and factors associated with alcohol use among high school students in Ethiopia Methods A cross-sectional study was conducted to assess the prevalence of alcohol use and its predictors among high school students in eastern Ethiopia in April 2010. A sample of students was taken from all schools based on their enrollment size. Prevalence estimates and their 95% confidence intervals were calculated. Logistic regression was performed to adjust and examine associations. Results A total of 1721 students participated in the study. The mean age of the study population was 16.4 (SD 1.6) years. A total of 372 (22.2%; 95% CI 20.2 - 24.2%) students drink alcohol. Of these, 118 (31.7%) were females and 254 (68.3) males. Multivariate analysis indicated that males (OR 2.09; 95% CI 1.45-3.00), older age (OR 1.16; 95% CI 1.01-1.34), having friends who used alcohol (OR 10.09; 95% CI 6.84-14.89) and living with people who use alcohol (OR 2.77; 95% CI 1.89-4.07) increased the odds of drinking among students. Conclusion There is a high level of alcohol use among high school students in the study area. Involvement of parents, health workers and school authorities are necessary to avert the problem. Specifically, their involvement in awareness campaigns and peer education training are important to encourage students to avoid alcohol use.